1995
DOI: 10.1038/375247a0
|View full text |Cite
|
Sign up to set email alerts
|

Direct stimulation of Jak/STAT pathway by the angiotensin II AT1 receptor

Abstract: The peptide angiotensin II is the effector molecule of the reninangiotensin system. All the haemodynamic effects of angiotensin II, including vasoconstriction and adrenal aldosterone release, are mediated through a single class of cell-surface receptors known as AT1 (refs 1, 2). These receptors contain the structural features of the G-protein-coupled receptor superfamily. We show here that angiotensin II induces the rapid phosphorylation of tyrosine in the intracellular kinases Jak2 and Tyk2 in rat aortic smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
433
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(455 citation statements)
references
References 27 publications
19
433
0
3
Order By: Relevance
“…60,61 Recent reports link Ang II, through the AT 1 receptor, to the Jak/STAT signalling pathway. 62 This is a significant observation since the Jak/STAT pathway has been previously identified for cytokine receptors which leads to transcriptional activation of early growth-response genes, 63 and is now possibly also an important signalling pathway through which Ang II mediates its proliferative effects. 64 Interaction of Ang II with the Jak/STAT pathway has been observed in rat aortic smooth muscle cells.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 93%
See 1 more Smart Citation
“…60,61 Recent reports link Ang II, through the AT 1 receptor, to the Jak/STAT signalling pathway. 62 This is a significant observation since the Jak/STAT pathway has been previously identified for cytokine receptors which leads to transcriptional activation of early growth-response genes, 63 and is now possibly also an important signalling pathway through which Ang II mediates its proliferative effects. 64 Interaction of Ang II with the Jak/STAT pathway has been observed in rat aortic smooth muscle cells.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 93%
“…64 Interaction of Ang II with the Jak/STAT pathway has been observed in rat aortic smooth muscle cells. 65 Ang II is able to rapidly phosphorylate tyrosine of the kinases Jak2 and Tyk2. Stimulation of Jak activity also leads to the phosphorylation of both STAT1 and STAT2 proteins, and subsequent translocation to the nucleus of the STAT1 protein.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 99%
“…59,60 This is a significant observation since the Jak/STAT pathway has been previously identified for cytokine receptors which leads to transcriptional activation of early growth-response genes, 61 and is now possibly also an important signalling pathway through which Ang II mediates its proliferative effects. 62 Generally, in response to ligand binding, Jak kinases associate with dimerized cytokine receptors, autophosphorylate, and activate signalling molecules via tyrosine phosphorylation, which in turn leads to association of the Jak substrates STAT1 and STAT2 and p48.…”
Section: At 1 Receptor and Signal Transductionmentioning
confidence: 98%
“…62 Interaction of Ang II with the Jak/STAT pathway has been observed in rat aortic smooth muscle cells. 60 Ang II is able to rapidly phosphorylate tyrosine of the kinases Jak2 and Tyk2. Stimulation of Jak activity also leads to the phosphorylation of both STAT1 and STAT2 proteins and subsequent translocation to the nucleus of the STAT1 protein.…”
Section: At 1 Receptor and Signal Transductionmentioning
confidence: 99%
“…Stimulation of AT 1 receptors has recently been shown to induce activation of JAK2 and to a lesser extent TYK2 in rat aortic smooth muscle cells and in the same studies the AT 1 receptor was shown to co-immunoprecipitate with JAK2, but not with JAK1 or TYK2. 99 …”
Section: Phospholipase C (Plc)mentioning
confidence: 99%